2019
DOI: 10.1038/s41598-019-44384-z
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional fracture resistance of ultrathin metallic glass films due to an intrinsic size effect

Abstract: Metallic glasses typically fail in a brittle manner through shear band propagation but can exhibit significant ductility when the sample size is reduced below a few hundreds of nanometers. To date the size effect was mainly demonstrated for free-standing samples and the role of extrinsic setup parameters on the observed behavior is still under debate. Therefore, in the present work we investigated the mechanical properties of polymer-supported sputtered amorphous Pd 82 Si 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Thin-film metallic glasses (TFMGs) are a new group of MGs which have been commonly fabricated by physical vapor deposition (PVD). With the process of vapor-to-solid by PVD, TFMGs are subjected to a much faster cooling rate compared to the process of liquid-to-solid by casting for bulk MGs. As a result, TFMGs not only possess the unique properties of MGs but also have a better glass-forming ability with a wider composition range. , Moreover, TFMGs can exhibit higher fracture resistance compared with their bulk MG counterparts because of the size effect. , Previously, we have confirmed the Au-based TFMGs as a plasmonic material, used nanoimprint to fabricate periodic nanostructures by taking advantage of the viscous flow behavior of TFMGs in the supercooled liquid region, and proved the feasibility of using Au-based TFMGs as LSPR-based sensor . In addition, we have studied the effects of crystallinity of Au-based TFMGs on SERS recently .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thin-film metallic glasses (TFMGs) are a new group of MGs which have been commonly fabricated by physical vapor deposition (PVD). With the process of vapor-to-solid by PVD, TFMGs are subjected to a much faster cooling rate compared to the process of liquid-to-solid by casting for bulk MGs. As a result, TFMGs not only possess the unique properties of MGs but also have a better glass-forming ability with a wider composition range. , Moreover, TFMGs can exhibit higher fracture resistance compared with their bulk MG counterparts because of the size effect. , Previously, we have confirmed the Au-based TFMGs as a plasmonic material, used nanoimprint to fabricate periodic nanostructures by taking advantage of the viscous flow behavior of TFMGs in the supercooled liquid region, and proved the feasibility of using Au-based TFMGs as LSPR-based sensor . In addition, we have studied the effects of crystallinity of Au-based TFMGs on SERS recently .…”
Section: Introductionmentioning
confidence: 67%
“… 36 , 37 Moreover, TFMGs can exhibit higher fracture resistance compared with their bulk MG counterparts because of the size effect. 37 , 38 Previously, we have confirmed the Au-based TFMGs as a plasmonic material, used nanoimprint to fabricate periodic nanostructures by taking advantage of the viscous flow behavior of TFMGs in the supercooled liquid region, and proved the feasibility of using Au-based TFMGs as LSPR-based sensor. 39 In addition, we have studied the effects of crystallinity of Au-based TFMGs on SERS recently.…”
Section: Introductionmentioning
confidence: 91%
“…This prompted us to check the transmittance spectra of light through the thinner TFMGs (i.e., those of thicknesses of 5, 10, and 20 nm). It was found that the TFMG gained optical transparency for thicknesses less than 5 nm, unlike the Pd-based TFMG [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Binary Zr-Cu based TFMGs have been reported to exhibit conductivity 1.4 and 8 times as large as that for the pure Zr and Cu films, respectively [ 17 ]. Meanwhile, it was demonstrated that Pd-based TFMGs were optically transparent at thickness less than 10 nm while being mechanically flexible [ 18 ]. Furthermore, Zr-Cu-Al-based TFMG was also reported to produce enhanced transmittance at near-infrared wavelengths by the addition of Si [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In compositionally homogeneous laminated FeP amorphous crystalline nanolaminates (213), extensive crack deflection at interfaces contributes to the highest strength and ductility values at an intermediate layer spacing of 40 nm. Size effects in fracture strength due to shear band inhibition in metallic glass thin films subject to 3% tensile strain occurred below 10 nm in PdSi films on polyimide, as assessed through the use of electrical resistance to detect the nucleation and growth of channeling cracks (214). This finding suggests that such films could be used in cycling applications.…”
Section: Metal Films and Elastic Plastic Fracturementioning
confidence: 92%